ESTRATÉGIAS DISCURSIVAS DE ENGAJAMENTO SOCIAL DO MOVIMENTO “ESCOLA SEM PARTIDO” NO FACEBOOK - Carneiro, Frederico de Souza Ramos (2020)
The research wants to understand the discursive strategies operated by the Escola Sem Partido (ESP) Movement by promoting the discourse against ideological indoctrination on Facebook with the purpose of engaging users. The use of persuasive means, ethos